2013
DOI: 10.1002/nau.22509
|View full text |Cite
|
Sign up to set email alerts
|

Levator plate descent correlates with levator ani muscle deficiency

Abstract: Worsening LAD score is associated with levator plate descensus and with decreasing levator plate descent angle. We can use levator plate descent angle along with the minimal levator hiatus and anorectal angle as objective measurements to assess levator ani muscle deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…The increasing angle of LPA and ARA also indicated the growing impairment of LA. 20 We also found movement angle of the lower segment of PVW was significantly different between stage 3 to 4 and stage 0 to 2; it could be the bulging vagina wall outside uncontrolled introitus. Bulging became the way to achieve balance on another level, which could be explained by the displacement of apex vagina being close to mid-PB, looking similar to that at stage 0.…”
Section: Discussionmentioning
confidence: 57%
“…The increasing angle of LPA and ARA also indicated the growing impairment of LA. 20 We also found movement angle of the lower segment of PVW was significantly different between stage 3 to 4 and stage 0 to 2; it could be the bulging vagina wall outside uncontrolled introitus. Bulging became the way to achieve balance on another level, which could be explained by the displacement of apex vagina being close to mid-PB, looking similar to that at stage 0.…”
Section: Discussionmentioning
confidence: 57%
“…After finishing the questionnaires, all participants underwent general overview of the pelvic floor which included the levator plate lift measurement by 2D transperineal ultrasound (BK ultrasound, Analogic, Peabody, MA) using the 8802 probe (6‐3 MHz; the distance between the levator plate and the posterior caudal aspect of the pubic symphysis) (Figure ). We also used the 8838 endovaginal probe (12‐4 MHz; the distance between the levator plate and the posterior vaginal epithelium) (Figure ) at rest and during the squeeze maneuver because this methodology has been shown to be highly reliable, repeatable, and correlate well with both the pelvic floor function and the levator ani anatomy . The measurement sequence is as follows:…”
Section: Methodsmentioning
confidence: 99%
“…We also used the 8838 endovaginal probe MHz; the distance between the levator plate and the posterior vaginal epithelium) ( Figure 2) at rest and during the squeeze maneuver because this methodology has been shown to be highly reliable, repeatable, and correlate well with both the pelvic floor function and the levator ani anatomy. 13 The measurement sequence is as follows:…”
Section: Methodsmentioning
confidence: 99%
“…As recent research has gravitated towards patient-oriented, outcome-based designs, objective assessment of PFMT with instruments such as a perineometer may be unnecessary. It has been shown that severe levator ani deficiency (LAD) increases the odds of POP sevenfold 6 7. It would be interesting to know if LAD status would predict intervention responders and non-responders.…”
Section: Commentarymentioning
confidence: 99%